Universal process diagrams for laser sintering of polymers. (1st February 2021) - Bierwisch, Claas; Mohseni-Mofidi, Shoya; Dietemann, Bastien; Grünewald, Moritz; Rudloff, Johannes; Lang, Marieluise
Abstract: The laser irradiation step and the thermo-viscous flow during selective laser sintering process applied to polymeric materials are analyzed both theoretically and by transient numerical simulations using the smoothed particle hydrodynamics method to spatially resolve individual powder particles. Taking into account the strongly different time scales of laser motion, thermal diffusion and viscous flow, normalized master curves for the transient melt pool temperature and the surface temperature are presented. Infrared camera measurements of the surface temperature confirm the validity of the theoretical framework. Based on these master curves a novel ratio of laser energy input and energy required to melt the polymer – the attenuation melt ratio (AMR) – is introduced, which puts material properties and process parameters into relation. Based on the AMR, normalized process diagrams, which relate depth and temperature of the melt pool to the laser energy input, are constructed. The process diagrams include process windows for optimal part properties. The predictive quality of the process windows is confirmed by the assessment of mechanical properties of laser sintered parts made of different polymers. Graphical abstract: Unlabelled Image Highlights: Dimensionless master curves of the surface temperature are derived from theory and validated by experiments. The attenuation melt ratio (AMR) is proposed which yields laser sintering process windows based on material properties. The validity of the AMR is confirmed by literature data for mechanical properties of PA12 and PEEK.